(untitled) (Research, Society and Development, 2023)
This article addresses the issue of sustainability in Brazilian organizations. In order to develop this study, a preliminary exploratory analysis was made of the concept of sustainability and its importance for balanced and responsible economic development in the business environment. The aim of this article is therefore to analyse the importance of sustainability in organizations and to present the main strategies that Brazilian companies are already adopting to make their operations more sustainable. To this end, this is a theoretical, exploratory and bibliographical study. Therefore, books, articles, reports and e-books were used as a source of research, which presented new perspectives on sustainable actions that could be implemented. In addition, four brazilian companies that stand out on the world stage in terms of their sustainable business practices were analyzed using an exploratory approach. In this way, the results of the research indicate that companies that adopt sustainable actions can improve their image, reduce costs and gain competitive advantages in terms of operating costs.